Monitoring power quality disturbances in microgrids - Gourab, Karmakar (2018)
Nowadays with the advent and increased usage of power electronics devices the effect of the power quality (PQ) disturbances for power utilities and customers is becoming a matter of great concern. These disturbances should be detected rapidly and accurately in order to protect the power system and the connected equipment. In this project, hybrid power system and experimental microgrid testbed present in CERL, EEE, NTU, Singapore is taken for the study of detection of various power quality disturbances using proposed DTCWT method. Various renewable energy sources such as wind energy system and solar photovoltaic are incorporated with distributed generators such as diesel engine generators to reduce the intermittency. Various energy storage devices such as flywheel and batteries are also integrated in the hybrid power system network to meet the load demand and improving the power management. The power quality disturbances are simulated and detected using system modelling with the help MATLAB/Simulink software tool as well as in real time digital simulator OPAL-RT by applying signal processing techniques such as standard wavelet transform and DTCWT. A comparison study is conducted for disturbance detection performance in case of proposed DTCWT technique as compared to conventional WT under various operating condition. Also, various performance parameters like SD and energy content are computed to make a distinction between system operating under the influence of power line disturbances and normal system operation based on a selected threshold value. Significant improvement in performance of DTCWT over the conventional wavelet transform is observed from the case study presented in the form of comparative analysis for detecting various power line disturbances. The results are validated in real time operating condition using OPAL-RT digital simulator.